Internationalization of companies in emerging countries and investment in the research center (Research, Society and Development, 2020)
Discussions on the theme Internationalization of companies have been relevant since the early 1990s. Thus, in view of the fact that the internationalization of companies is a phenomenon with significant expansion since then in a globalized scenario, this article aims to contribute to update the debate on the subject. Structuring the following issues: (1) globalization, (2) the new world economic order, (3) the link between foreign trade and (4) foreign direct investment, as well as, and (5) internationalization as a competitive strategy for strengthening companies in emerging countries through the development of research centers. The methodology used was exploratory and descriptive. As a result of this work, 4 hypotheses are presented and suggested as future studies: That the growth and development of international trade does not boost internationalization in an isonomic way, that emerging countries are the main attractors of international investment, that there is a need to predict the risks present in the internationalization of companies, and finally, that a current and competitive strategy would be the installation of Research Centers in emerging countries that favor the internationalization of companies.